Enhancing the Stabilization Potential of Lyophilization for Extracellular Vesicles. Issue 5 (26th July 2021) - Trenkenschuh, Eduard; Richter, Maximilian; Heinrich, Eilien; Koch, Marcus; Fuhrmann, Gregor; Friess, Wolfgang
Abstract: Extracellular vesicles (EV) are an emerging technology as immune therapeutics and drug delivery vehicles. However, EVs are usually stored at −80 °C which limits potential clinical applicability. Freeze‐drying of EVs striving for long‐term stable formulations is therefore studied. The most appropriate formulation parameters are identified in freeze‐thawing studies with two different EV types. After a freeze‐drying feasibility study, four lyophilized EV formulations are tested for storage stability for up to 6 months. Freeze‐thawing studies revealed improved colloidal EV stability in presence of sucrose or potassium phosphate buffer instead of sodium phosphate buffer or phosphate‐buffered saline. Less aggregation and/or vesicle fusion occurred at neutral pH compared to slightly acidic or alkaline pH. EVs colloidal stability can be most effectively preserved by addition of low amounts of poloxamer 188. Polyvinyl pyrrolidone failed to preserve EVs upon freeze‐drying. Particle size and concentration of EVs are retained over 6 months at 40 °C in lyophilizates containing 10 mm K‐ or Na‐phosphate buffer, 0.02% poloxamer 188, and 5% sucrose. The biological activity of associated beta‐glucuronidase is maintained for 1 month, but decreased after 6 months. Here optimized parameters for lyophilization of EVs that contribute to generate long‐term stable EV formulations are presented. Abstract : Extracellular vesicles (EVs) are lyophilized to improve long‐term stability. Therefore, important formulation principles are evaluated with respect to colloidal stability and biological activity of associated beta‐glucuronidase. In vitro studies confirmed EV stability for one month while particle size and concentration can be preserved for six months.